An Analysis of the Impact of Digital Transformation on the Unemployment Rate in the Kingdom of Saudi Arabia during the period (2000-2021) - Alateeg, Fatimah Fahd; Halawani, Abrar Adel (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to analyze the impact of applying digital transformation on the unemployment rate in the Kingdom of Saudi Arabia during the period (2000-2021). In order to investigate the relationships, a multiple regression analysis model was described, to express the relationship between the unemployment rate as a dependent variable, and the independent variables associated with digital transformation, which were chosen based on previous studies and the efforts of researchers, represented in the number of transactions executed with mada card, number of patents, number of internet users, and spending on research and development. By specifying the variables and hypotheses to be tested, descriptive tests were conducted, and the general trend of the variables was identified by the statistical program E-views. As expected, the results showed an inverse relationship between the unemployment rate and the number of mada card transactions. The study also showed -contrary to expectations- that the number of patents, the number of Internet users, and spending on research and development, did not affect unemployment rates in the KSA, during the study period. The study recommended the necessity of working to develop the infrastructure of the information and communications technology sector, raising the efficiency of intellectual and cognitive human resources, qualifying them to manage and keep pace with rapid technical development, and encouraging investments in the information and communications technology sector, because of its fundamental role in keeping pace with development and digital transformation, which positively affects the reduction of unemployment rate.
Keywords: digital transformation; technical transformation governance; technical unemployment; digital economy